Implementation of Islamic Values in Digital Transformation of Sharia Business in the Modern Economic Era - Zainol Fata (International Conference on Islamic Economic (ICIE), 2025)
Islam is a comprehensive and perfect religion that encompasses all aspects of human life, including the fields of economics and business. Its teachings emphasize the importance of economic independence through hard work, honesty, and adherence to Sharia principles. Along with the rapid advancement of technology, digital transformation has become a significant phenomenon influencing the Islamic business system in the modern era. This study aims to analyze the implementation of Islamic values in the process of digital transformation within Sharia-based businesses, as well as to examine the challenges and opportunities arising amidst the development of the digital economy. The research employs a qualitative approach through a literature review method by examining various sources related to the topic. The findings indicate that digital transformation offers great opportunities for the development of Islamic business through innovations such as Sharia fintech, halal e-commerce, and Islamic-based digital marketing. These innovations expand market reach, improve efficiency, and strengthen an economic system grounded in justice and transparency. However, digitalization also poses challenges, such as the potential emergence of riba, gharar, and maysir if not properly regulated according to Sharia principles. Therefore, the application of values such as justice (al-‘adl), trust (amanah), honesty (ash-shidq), and excellence (ihsan) becomes essential to ensure that digital business remains aligned with maqāṣid al-syarī‘ah. Thus, digital transformation in Islamic business is not merely an effort toward economic modernization but also a means to realize an ethical, inclusive, and sustainable business system in accordance with Islamic teachings